RETRACTED: Bactericidal/Permeability-Increasing Protein Improves Cognitive Impairment in Diabetic Mice via Blockade of the LPS-LBP-TLR4 Signaling Pathway - Sun, Qin; Li, Tingxin; Li, Yamei; Wei, Lingling; Zhang, Min; Deng, Shaoping (Frontiers in Physiology, 2021)
Emerging evidence suggests that BPI is closely related with diabetes with cognitive impairment. BPI exerts effects on diabetes with cognitive impairment with unclear mechanisms. This study aims to investigate the role of BPI playing in diabetes with cognitive impairment. The high fat diet (HFD) and streptozotocin (STZ) were used to induce mouse models of diabetes. The modeled mice were then injected with overexpressed BPI and LPS adenovirus. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) and western blot analysis were used to examine the expression of the expression of BPI, LPS, LBP, CD14 and TLR4 in diabetes models. The insulin levels in plasma and serum levels of inflammatory factor were examined by ELISA. Glucose tolerance test and insulin resistance test were used to measure systemic insulin sensitivity. The hippocampal tissue injury and apoptosis of cells were examined by HE and TUNNEL staining. Upregulated LPS and activated LPS-CD14-TLR4 signaling pathway were found in diabetic mice. HFD mice following LPS treatment showed significantly aggravated inflammatory response, increased expression of Bax and Aβ in hippocampal tissues, cognitive decline, fasting blood glucose, plasma insulin, glucose tolerance and insulin tolerance, the degree of hippocampal tissue injury as well as cell apoptosis but decreased expression of Bcl-2. However, over-expressed BPI could rescue the aforementioned results driven by LPS treatment, Taken together, the cognitive impairment in diabetic mice can be relieved by abundant BPI expression with the LPS-LBP-TLR4 signaling pathway blockade.